Comparative studies on metabolic profile of anestrus and normal cyclic Haryana cows - SINGH, C P; SAXENA, ATUL; PRASAD, SHIV; PRASAD, J K (The Indian Journal of Animal Reproduction, 2023)
Twenty seven Haryana cows were selected (17- anestrus & 10- nonnal cyclic) from the university farmfor the study of metabolic profile in relation to anestrus. Parameter studied were haemoglobin (Hb ), serumglucose, total protein, calcium (Ca), inorganic phosphorus (Pi) and calcium to phosphorus ratio (Ca: P). It wasfound that levels ofHb were significantly higher (P
Keywords: Metabolic profile; Hb; Serum glucose; Calcium; Inorganic phosphorus; Infertility; Cows